Volatilomics with SPME/GC-MS method for halal species authentication of meat products - Pertiwi, Chafiyani Wulan; Yuliana, Nancy Dewi; Indrasti, Dias (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2025)
The demand for animal-based food, particularly meat, continues to increase. However, certain types of meat are relatively expensive, which encourages the practice of adulterating non-halal meat to reduce production costs. Therefore, the use of analytical methods to detect the presence of non-halal species in products is necessary, especially for the halal certification process. Volatile compound-based halal authentication using SPME-GC-MS (Solid Phase Microextraction-Gas Chromatography-Mass Spectrometry) has been a focus of research in recent years due to its speed and simplicity. However, due to the large amount of data involved, chemometric applications cannot be separated. Therefore, this article aims to review the principles and applications of the SPME-GC-MS method in the detection of meat from certain species for the purpose of halal authentication. The data synthesis process in this article was performed by comparing relevant journals that met the inclusion and exclusion criteria. The database was obtained through Google Scholar, PubMed, Science Direct, MDPI, and Springer. The SPME-GC-MS method combined with chemometrics can clearly classify different types of meat and meat products from different species. Therefore, this method can be used for the halal authentication of meat products. However, quantification of the marker compound is required to obtain more precise results.